GAMBARAN PENGETAHUAN DAN SIKAP SISWA SMA NEGERI 1 JAMBI KOTA JAMBI TENTANG PERILAKU SEKSUAL TAHUN 2008 - Cek Masnah (Jurnal Ilmiah Universitas Batanghari Jambi, 2009)
Teenagers, most of wom are high school students aged beetwen 15-18 years, do not have adequate knowledge abaout reproduction and sexuality. As a result, they do pre marital sex without any contraception. Consequently, they suffer from unwanted pregnancy, abortion and HIV/AIDS infection. The purpuse of  this research is to investigate the sexual behaviour of high school students. The population is 296 of SMAN 1 Jambi students in 2008. the sample is 74 (25%) of them which is randomly selected. The analysis shows that 55,4% of respondents admits to have good knowledge about sexual behaviour and 44,6% bad sexual knowledge. The analysis also shows that 51 (69%) of the respondents have positive attitude towards sexual behaviour and 23 (31%) negative attitudes. It is sugested that to improve students knowledge about sexual behaviour government through school add  the extracurriculer activities with more education on biology and reproduction anatomy. It’s also suggested that religion norms get more emphasis.